Treatment and radiologic follow-up of panosteitis in a german shepherd dog - Yılmaz Koç; Fahrettin Alkan; Fatih M. Birdane; Zeki Oğurtan (Eurasian Journal of Veterinary Sciences)
In this case report, clinical and radiologic follow-up of panosteitis was described in a German Shephard dog. The cause of panosteitis is unknown. Panosteitis occurs especially in young large or giant breeds of dogs. The diagnosis of panosteitis is confirmed through clinical, radiolagical and laboratuary findings. Flunixine meglumine were used to treat the disease.